Stability of steady states in a model of pleasant monetarist arithmetic - Marco Espinosa-Vega; Steven Russell (Federal Reserve Bank of Atlanta, 2001)
In this paper the authors study the stability properties of the alternative steady-state equilibria that arise in a neoclassical production model that delivers pleasant monetarist arithmetic. They show that if the government's monetary policy rule involves a fixed money supply growth rate, then "pleasant arithmetic" steady states—steady states from which a permanent increase in the money growth and inflation rates is associated with a permanent decrease in the real interest rate and a permanent increase in the level of output—are dynamically stable.
Keywords: 330; Econometric models; Monetary policy